2008
DOI: 10.1128/jcm.00016-08
|View full text |Cite
|
Sign up to set email alerts
|

Lagos Bat Virus in Kenya

Abstract: During lyssavirus surveillance, 1,221 bats of at least 30 species were collected from 25 locations in Kenya. One isolate of Lagos bat virus (LBV) was obtained from a dead Eidolon helvum fruit bat. The virus was most similar phylogenetically to LBV isolates from Senegal (1985) and from France (imported from Togo or Egypt; 1999), sharing with these viruses 100% nucleoprotein identity and 99.8 to 100% glycoprotein identity. This genome conservancy across space and time suggests that LBV is well adapted to its na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
151
2
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(174 citation statements)
references
References 48 publications
16
151
2
5
Order By: Relevance
“…Total RNA was extracted from the oral swabs (n = 931) and subjected to nested reverse transcription-PCR, as described previously (10). We used primers designed for the nucleoprotein genes of LBV, MOKV, and WCBV.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from the oral swabs (n = 931) and subjected to nested reverse transcription-PCR, as described previously (10). We used primers designed for the nucleoprotein genes of LBV, MOKV, and WCBV.…”
Section: The Studymentioning
confidence: 99%
“…We used 4-well (6-mm) Tefl oncoated glass slides (Cel-Line, Erie Scientifi c, Portsmouth, NH, USA) as described elsewhere (10). Previous tests for RABV neutralizing antibodies have demonstrated that re-sults of this micromethod are comparable to those of the classical test in chamber slides.…”
Section: The Studymentioning
confidence: 99%
“…Both samples that demonstrated neutralizing activity against MOKV came from E. helvum in Karfi. Other studies in Africa record about 38% virus neutralizing activity to LBV among fruit bats in Ghana and Kenya (Hayman et al, 2008: Kuzmin et al, 2008.…”
mentioning
confidence: 92%
“…Five other lyssavirus species, including Lagos bat virus (LBV), Duvenhage virus (DUVV), European bat lyssaviruses 1 and 2, and Australian bat lyssavirus have been reported in other parts of the world (WHO, 2005). More recently, four new putative lyssavirus species (Aravan, Kudjand, Irkut, and West Caucasian bat viruses) have been identified in bats (Kuzmin and Rupprecht, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation